2022
DOI: 10.1155/2022/1838468
|View full text |Cite
|
Sign up to set email alerts
|

Taekwondo Action Recognition Method Based on Partial Perception Structure Graph Convolution Framework

Abstract: Action recognition in Taekwondo competitions and training is an important task, which can provide a very valuable reference factor for technicians, athletes, and coaches. We propose a graph convolution framework with part of the perception structure to recognize, decompose, and analyze Taekwondo actions. Taking advantage of the long short-term memory of a part of the perception structure, the recognized Taekwondo actions are marked in time series, and then features are extracted from the graph convolution leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Through this operation, the defects of manual design features are avoided, and the spatial features on the time series are obtained. [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Through this operation, the defects of manual design features are avoided, and the spatial features on the time series are obtained. [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…The paper by Liang & Zuo (2022) proved that movement classifications from videos and mapping them to score a Taekwondo sparring (fighting) match are also possible. They introduced a graph convolution framework to recognize, segment, and evaluate Taekwondo actions with a specific part of the perception structure.…”
Section: Usagementioning
confidence: 99%
“…Kong et al [ 15 ] proposed an automatic analysis framework for broadcasted Taekwondo videos, integrating a structure-preserving object tracker with a principal component analysis (PCA) network. Liang et al [ 16 ] explored a novel evaluation method for Taekwondo competitions combining long short-term memory (LSTM) with a spatial temporal graph convolutional network (ST-GCN). Recently, Lee et al [ 17 ] reported over 80% recognition accuracy using a convolutional neural network (CNN)-based model that processes a sequence of key-frame images to identify basic Taekwondo unit actions.…”
Section: Introductionmentioning
confidence: 99%